2018
DOI: 10.31557/apjec.2018.1.1.19
|View full text |Cite
|
Sign up to set email alerts
|

CARcinogen EXposure: CAREX

Abstract: Cancer is the second common cause of death worldwide and a significant ratio of all cancers is related to occupational and living environments. On the other side, cancer prevalence could be controlled and prevented via policies to improve occupational and living environments. However, a main challenge in prevention of occupational cancer is the lack of knowledge about the exposure rate and number of exposed persons. CAREX database, which is established by the program of Europe against cancer, provides informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
(126 reference statements)
2
11
0
Order By: Relevance
“…Given the correlation between sleep anxiety with the duration of television viewing and the use of electronic media [36], seems to spending more time on television decrease the opportunity of child's sleeping and increase sleep anxiety [19]. The nocturnal awakening of children in the present study is similar to other studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The evolution of reducing nighttime awakenings is from birth to 3 years old and there is no difference between Asian and non-Asian children [37].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Given the correlation between sleep anxiety with the duration of television viewing and the use of electronic media [36], seems to spending more time on television decrease the opportunity of child's sleeping and increase sleep anxiety [19]. The nocturnal awakening of children in the present study is similar to other studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The evolution of reducing nighttime awakenings is from birth to 3 years old and there is no difference between Asian and non-Asian children [37].…”
Section: Discussionsupporting
confidence: 85%
“…Many studies have also suggested that stress itself is an environmental factor in cancer. Therefore, controlling the determinants of sleep habits from the perspective of cancer reduction is also important [12][13][14][15][16]. In previous studies, factors such as maternal education, maleness, low birth weight, presence of more than one older sibling, television viewing more than one hour in the evening, were associated with insomnia in toddlers [17].…”
Section: Introductionmentioning
confidence: 99%
“…There are many costs incurred each year due to occupational accidents, in short, most of them are due to lack of safety. Which in addition to financial losses also leaves irreparable spiritual and human losses [1][2][3][4][5][6][7][8][9]. Occupational accidents usually occur in hospitals that may be due to neglect, Failure, carelessness, fatigue or other factors, without prior warning.…”
Section: Introductionmentioning
confidence: 99%
“…These risks are particularly relevant to the production and use of chemicals in various processes [25][26]. To avoid the harmful side effects of these chemicals, it is important to observe precautions and control measures when handling them [27][28][29][30][31]. In a study of 245 new occupational asthma samples from 1976 to 1992, 39 percent with hexamethylene diisocyanate (HDI), 39 percent with diphenyl methane diisocyanate (MDI) and 17 percent with toluene diisocyanate (TDI) exposure [32].…”
Section: Introductionmentioning
confidence: 99%